A new Iberian inscription on a spindle whorl from Puig Ciutat (Oristà, Barcelona) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The paper offers an edition of an unpublished Iberian inscription on a spindle whorl, which was found among the debris of a room at the settlement of Puig Ciutat, whose end is dated to the mid-first century BCE. The reading of the inscription poses serious problems, because the object is highly worn, but there is no doubt about the presence of the term kaśtaun at the beginning of the text. This word is attested on four other Iberian spindle whorls and seems to be characteristic of the lexicon appearing on this type of instrumenta. The paper also presents a single-letter graffito on the foot of a Calenian black-glazed cup.
Keywords: Iberian Epigraphy; Earthenware; Iberian Language; Graffito; kaśtaun